Cartilage Restoration Practical Clinical Applications (Springer International Publishing, 2018)
Now in a revised and expanded second edition, this practical text utilizes the most current evidence and knowledge of articular cartilage as the basis for clinical interventions for cartilage repair and restoration, combining an overview of clinical research and methodologies with clinical cases to help guide the orthopedic treatment and care of patients presenting with cartilage issues. Carefully updated chapters discuss the state-of-the-art in cartilage anatomy, defects and imaging, current tibiofemoral and patellofemoral surgical options, debridement and marrow stimulation, osteochondral autografts and allografts, osteotomies, cell therapy, and meniscal transplantation. New chapters explore new surgical treatment strategies and revision for failed cartilage repair, case vignettes presenting real-life treatment decisions and outcomes, and rehabilitation protocols following cartilage repair. Written and edited by experts in the field and bringing the most recent literature and research to bear, Cartilage Restoration remains a valuable resource on joint preservation for orthopedic surgeons, residents, and fellows, sports medicine specialists and rheumatologists.